Isochoric freezing: advantages and research opportunities in the food industry - Chaves-Quesada, José (2023)
Introduction. Isochoric freezing (at constant volume) is a novel technology that has been evaluated in different studies to demonstrate the possible benefits for the food industry. Objective. To present an overall summary about the frozen food market, the freezing technologies currently used, as well as the emerging ones, and delve into the fundamental theories of isochoric freezing and the advantages in the food industry compared to traditional freezing systems and to show the possible fields of research related to this technology. Development. This work was carried out in Costa Rica between February 2022 and June 2022, it describes the general context of the frozen food market, the technologies used in the industry, the thermodynamic principles of the isochoric technology, the physicochemical, microbiological and energetical advantages, and ends with the possible fields of research and disadvantages recently found. Conclusion. Isochoric freezing presents important advantages compared to the current freezing processes in the food industry, however, it is necessary to perform more research related to microbiological aspects, as well as to optimize the process parameters and equipment to generate a change in the global food freezing system.